2012
DOI: 10.1089/dia.2012.0061
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Fasting in Diabetes Patients on Insulin Pump Therapy Augmented by Continuous Glucose Monitoring: An Observational Real-Life Study

Abstract: This study confirms the advantages provided by insulin pump use in patients with diabetes were enhanced by the use of continuous glucose monitoring. We provided more evidence-based advice on how best to adjust the insulin pump during fasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 16 publications
3
58
0
Order By: Relevance
“…Our findings are similar to the findings of other studies (2)(3)(4) in that the majority of patients with T1D could fast 15 or more days during Ramadan. Nonetheless, symptomatic hypoglycemia was reported and resulted in breaking the fast in 15% of the days.…”
supporting
confidence: 92%
“…Our findings are similar to the findings of other studies (2)(3)(4) in that the majority of patients with T1D could fast 15 or more days during Ramadan. Nonetheless, symptomatic hypoglycemia was reported and resulted in breaking the fast in 15% of the days.…”
supporting
confidence: 92%
“…Two small observational studies reported that patients taking ultralente or insulin lispro could fast without experiencing severe hypoglycaemic episodes [61,62]. More recent studies in patients using insulin pumps reported no cases of severe hypoglycaemia, although some episodes of hypoglycaemia required the fast to be broken and adjustments to the basal rate were needed [63,64]. If patients with T1DM insist on fasting, then the recommended adjustments to insulin medication and/or dosing regimen during Ramadan are outlined in Fig.…”
Section: Adults With T1dmmentioning
confidence: 99%
“…The use of an insulin pump helps to provide a continuous basal rate of insulin during the fasting period and to rapidly cover for meals intake after the breaking of the fast. In one study, patients on insulin pumps were monitored during Ramadan with a continuous glucose-monitoring (CGM) device 20. There was no significant increase in the risk of hypoglycemia when comparing the periods before, during, and after the end of fasting.…”
Section: Use Of Glucose-lowering Medications During Ramadanmentioning
confidence: 99%